Elements of social harmony in Rig veda - Balakailasanathasarma, M. (International Journal of Sanskrit Research 2022; 8(5): 31-34, 2022)
Vedic literature in Sanskrit has been serving the entire world in humanistic efforts. Sri Lanka is a nation of different religions and diverse cultures and has a tradition going back to several centuries The Vedic literature is treated to be the oldest literature of the world. The Objective of this study is to identify some evidences of Social Harmony concepts in Rig Vedic Literature. This Study focused on Rigveda considering its early origin and recognition among the scholars. Mixed method including descriptive and analytical method is used to identify elements of concepts. This research presents a brief outline of the elements of social harmony, as we find it in ancient Vedic literature. Findings of the study prove that the Vedic literature speaks the ways of attaining spirituality by establishing a harmony with all beings. They built the treasure house full of human wisdom, social welfare, unity, peace and prosperity, instead of personal gain or internal prosperity at large. Vedic verses that prays for different aspects of the universal; happiness and peace. Among these elements, Universal pleasure, Collective actions of people, Stimulation of mental power, Path to wealth & happiness, Conservation of Resources, Enlightened people, Sharing of Wealth, Eco friendly life, Sustainable good life and Government, Gathered Long life, Happiness in mind and life are remarkable. These elements could be considered similar to current social harmony aspects.
Keywords: Social harmony; Vedic literature; Hindu ethics; Rigveda